2023
DOI: 10.1097/coc.0000000000000990
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on Overall Survival Among Children With Wilms Tumor

Abstract: Objectives: International trials have reported conflicting findings on whether the association between age and worse overall survival (OS) among children with Wilms tumor (WT) is due to age as an independent prognostic factor or the observation of more advanced disease at older ages. We sought to further elucidate this relationship using a population-based registry analysis. Methods: The Surveillance, Epidemiology, and End Results database was queried for all patients diagnosed with WT under the age of 20. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…[22][23][24] Compared to previous studies, we found a higher risk of distant metastasis for CCSK (13% vs. 4%-7%). 15,17 The association of older age, larger TV and more advanced tumour stage in our series of WT was recently also reported in a large SEER cohort of 3463 patients 25 (Supplemental Consistent with previous work, we identified CMN as the most common kidney tumour up to 3 months of age. 13 Thereafter the frequency decreases significantly as reported by others.…”
Section: Incidence Bilaterality and Metastasissupporting
confidence: 90%
See 1 more Smart Citation
“…[22][23][24] Compared to previous studies, we found a higher risk of distant metastasis for CCSK (13% vs. 4%-7%). 15,17 The association of older age, larger TV and more advanced tumour stage in our series of WT was recently also reported in a large SEER cohort of 3463 patients 25 (Supplemental Consistent with previous work, we identified CMN as the most common kidney tumour up to 3 months of age. 13 Thereafter the frequency decreases significantly as reported by others.…”
Section: Incidence Bilaterality and Metastasissupporting
confidence: 90%
“…Compared to previous studies, we found a higher risk of distant metastasis for CCSK (13% vs. 4%–7%) 15,17 . The association of older age, larger TV and more advanced tumour stage in our series of WT was recently also reported in a large SEER cohort of 3463 patients 25 (Supplemental Table 3).…”
Section: Discussionsupporting
confidence: 66%
“…During the Covid pandemic there was a higher proportion of advanced disease and larger tumor volumes in WT, but the time to the start of treatment was not delayed. 17 In older patients (adolescents and young adults) with WT a higher tumor burden can be found 18 which may be caused by a longer time to diagnosis also resulting in a poorer outcome. preventive medical examination or screening programs for CPSs.…”
Section: Discussionmentioning
confidence: 99%
“…Welter et al also discussed the importance of early diagnosis in CPS associated with WT 27 being in accordance with our findings that patients with tumor-related symptoms have larger tumor volumes and more metastatic disease. In addition, Qian et al 18 could show that older age in patients diagnosed with WT is independent of other factors associated with worse OS, which further emphasizes the need to ensure early diagnosis, In osteosarcoma, the prognostic impact of diagnostic and treatment delay resulting in higher tumor load was analyzed by Vasquez et al finding that latency to diagnosis did not influence EFS and OS, but outcome was poorer in patients with a longer time to complete treatment. 28 This time-period as a measure for treatment intensity was not analyzed in our study.…”
Section: Outcome Analysismentioning
confidence: 99%